Pengembangan Aplikasi Android untuk Meningkatkan Efisiensi dan Efektivitas Proses di Sentra Inovasi dan Inkubator Bisnis - Yunda Heningtyas; Lofanny Wahyu Dandi; Astria Hijriani; Bambang Hermanto (Jurnal Pepadun, 2022)
The development of the Sentra Inovasi dan Inkubator Bisnis (SIKUBIS) system is a project of the Institute for Research and Community Service at the University of Lampung. This project aims to provide a platform for businesses to access various resources and support in the form of information, guidance, and networking opportunities. The SIKUBIS system will be designed to be user-friendly and accessible through mobile devices, making it convenient for businesses to access and utilize the resources provided. The development of this system will also aim to enhance the efficiency and effectiveness of the SIKUBIS center in supporting the growth and development of businesses. Based on the results of application development, black-box testing, and usability testing, this research has succeeded in creating the SIKUBIS application which can be used by lecturers, students, and educational staff in the campus environment to develop their business. Overall, the SIKUBIS system will serve as a valuable tool for businesses to access the resources and support they need to succeed and thrive in today's competitive market.